Cardiac magnetic resonance imaging of primary cardiac tumors - Li, Xiaodan (Quant Imaging Med Surg, 2020)
Cardiac magnetic resonance (CMR) offers superior advantages in cardiac imaging due to supplying a greater field of view, excellent soft-tissue imaging, and multiplanar imaging capabilities. CMR imaging can evaluate the characteristics of cardiac tumors by visualizing the relationship between the tumor and surrounding tissues, and plays a vital role in assisting the formulation of the surgical plan, the assessment of tumor progression, and the monitoring of postoperative tumor recurrence and metastasis. In this review, we present the clinical manifestations and imaging features of different cardiac tumors. The superior performance of CMR in preoperative diagnosis, surgical treatment, and postoperative follow-up of patients with heart tumors are also highlighted.